# What is the inverse function of #y=2-x#?

This gives us:

By signing up, you agree to our Terms of Service and Privacy Policy

To find the inverse function of ( y = 2 - x ), we swap the roles of ( x ) and ( y ) and then solve for ( y ).

Original function: ( y = 2 - x )

Swap ( x ) and ( y ): ( x = 2 - y )

Now, solve for ( y ):

[ x = 2 - y ] [ x - 2 = -y ] [ y = 2 - x ]

Therefore, the inverse function of ( y = 2 - x ) is ( y = 2 - x ), which is the same as the original function.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the vertical, horizontal or slant asymptotes for #f(x) = (2x^2 + x + 2) /( x + 1)#?
- How do you identify all asymptotes or holes for #y=(x^3-1)/(x^2+2x)#?
- How do you find the end behavior of #9x^4 - 8x^3 + 4x#?
- What is the range of the function #y = x^2#?
- How do you find the vertical, horizontal or slant asymptotes for # [(9x-4) / (3x+2)] +2#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7